Residual Stress Analysis in PVD Coated Austempered Ductile Iron - Colombo, Diego Alejandro (2013)
The aim of this work is to study residual stresses (RS) in PVD TiN and CrN coated ADI substrates with different nodule counts, austempering temperatures and surface finishing methods (grinding and polishing). Coatings were applied by arc ion plating using an industrial reactor and different sets of processing parameters. Residual stress measurements were performed by x-ray diffraction using the sin2 ψ method along two principal axes on the samples surface (parallel and perpendicular to the substrate abrasion direction). The film thickness, hardness and adhesion of each coated sample were also evaluated. The results obtained indicate that RS in TiN and CrN coated samples are compressive irrespective of the different substrates, surface finishing methods and processing parameters utilized. The parallel and perpendicular RS do not vary significantly, indicating a rotationally symmetric biaxial stress state. The RS of the coated samples are not influenced by the different substrate characteristics regarding microstructure, hardness and surface roughness. The microhardness and RS of TiN and CrN coated samples increase with film thickness. The increase in substrate temperature together with the decrease in the values of BIAS voltage, arc current and chamber pressure lead to microhardness and RS reduction. Grinding produces surface hardening and reduction of the compressive RS in the substrates, but causes no variations in the RS of the TiN and CrN coated samples. The adhesion strength quality of TiN and CrN coatings to ADI substrates can be related to indices ranging from HF1 to HF2.